An Icosahedral 55-Atom Iron Hydride Cluster Protected by Tri-tert-butylphosphines - Higaki, Tatsuya; Tanaka, Kanata; Izu, Hitoshi; Oishi, Shunya; Kawamoto, Koki; Tada, Mizuki; Sameera, W. M.C.; Takahata, Ryo; Teranishi, Toshiharu; Kikkawa, Soichi; Yamazoe, Seiji; Shiga, Takuya; et al. (Journal of the American Chemical Society, 2025)
Nanoclusters are nanometer-sized molecular compounds characterized by significant metal-metal bonding and low average oxidation states, and they exhibit unique properties distinct from those of small metal complexes or nanoparticles. Unlike noble metals stable in metallic forms, the synthesis of nanometer-sized iron clusters has been precluded by the relatively weak iron-iron bonds and the high reactivity of low oxidation state iron, despite the extensive history of molecular iron compounds. Here, we report the synthesis and characterization of a cationic 55-atom iron cluster with a 1.2 nm icosahedral core. Its 12 vertices are occupied by tri-tert-butylphosphines, while multiple hydrides cover the surface. This core can be viewed as a substructure of the face-centered cubic (fcc), in contrast to the body-centered cubic (bcc) for the stable bulk phase. This work reveals a stable structure and fundamental properties of a nanometer-sized iron cluster, which have remained elusive for decades, and the simple synthetic protocol provides a route to explore molecular nanochemistry.
CRIS-Team Scopus Importer:2025-01-31